Pendampingan Implementasi Aplikasi e-Bangkit Berbasis Android untuk Meningkatkan Efisiensi dan Implementasi P5 Berbasis Kearifan Lokal di KKG Aluh-aluh Kabupaten Banjar - Noorhapizah; Yogi Prihandoko; Agus Rifani Syaifuddin; Diani Ayu Pratiwi; Mubarok (Jurnal Pengabdian Masyarakat - PIMAS, 2025)
This article aims to describe the mentoring program for the implementation of the e-BANGKIT Android-based application for teachers in the Aluh-aluh Teacher Working Group (KKG) in carrying out the Pancasila Student Profile Strengthening Project (P5) based on local wisdom. The program was motivated by the limited educational infrastructure in wetland areas, which hampers efficiency in administration and documentation of learning. The applied methods included workshops, intensive training, field assistance, the establishment of digital school driving teams, and periodic evaluations. These stages were designed to enhance teachers’ digital literacy, strengthen competencies in integrating technology, and ensure the program’s sustainability after the mentoring phase. The results show that the use of e-BANGKIT simplifies P5 administration, improves teachers’ skills in managing digital data, and facilitates systematic documentation of local wisdom–based activities. Moreover, the formation of digital school driving teams plays a crucial role in ensuring the continuity of application utilization. In conclusion, this mentoring program successfully strengthened teachers’ digital literacy, supported the implementation of the Merdeka Curriculum, and provided a practical solution to overcome educational infrastructure limitations in the Aluh-aluh region.